2010
DOI: 10.3109/17477160903540735
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adolescent overweight/obesity in Ho Chi Minh city

Abstract: Family/parental factors as well as children's lifestyle should be taken into account when planning interventions to prevent adolescent obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 28 publications
8
28
2
1
Order By: Relevance
“…Similar to previous studies [5759], females had a higher overweight and obese prevalence than males while the reverse was true for underweight. This is different however to findings of previous studies in high income countries [60, 61] which showed a higher prevalence of overweight among adolescent boys compared to girls. In one of these studies, “obesity prevalence varied from 1.1% (Dutch and Danish girls) to 10.7% (Portuguese boys) and from 0.3% (Dutch girls) to 6.2% (Portuguese boys) respectively” [61].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to previous studies [5759], females had a higher overweight and obese prevalence than males while the reverse was true for underweight. This is different however to findings of previous studies in high income countries [60, 61] which showed a higher prevalence of overweight among adolescent boys compared to girls. In one of these studies, “obesity prevalence varied from 1.1% (Dutch and Danish girls) to 10.7% (Portuguese boys) and from 0.3% (Dutch girls) to 6.2% (Portuguese boys) respectively” [61].…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is somewhat counter-intuitive and is significantly different from previous studies [34, 60] which have shown the opposite. However, one study [48] showed that frequent involvement in sports was not associated with a lower BMI in Egyptian youth.…”
Section: Discussioncontrasting
confidence: 99%
“…The duration of recall time, collection techniques and quantification of food intake data were observed to differ to a large extent across different studies. Food frequency questionnaires are the most commonly used method of assessing dietary intake in schoolchildren and adolescents in developing countries [19,20,21,37,38,39,40,41,42,43,44,45,46,47,48]. The use of single 24-hour recalls was also relatively common [5,7,13,42,49,50], while some studies used repeated 24-hour recalls [51,52,53,54,55,56].…”
Section: Resultsmentioning
confidence: 99%
“…i A gradient for higher TV, video games, sedentary bouts, sedentary breaks, screen time, and studying with unfavourable body composition was observed in 30 studies (Hong et al 2010;Kuhle et al 2010;Pitrou et al 2010;Carson and Janssen 2011;Kimbro et al 2011;Leatherdale and Papadakis 2011;Mushtaq et al 2011;Sisson et al 2011;Carson and Janssen 2012;Drake et al 2012;Kuriyan et al 2012;Masse et al 2012;Rey-Lopez et al 2012;Taber et al 2012;Tin et al 2012;Zhang et al 2012;Braithwaite et al 2013;Cameron et al 2013;Colley et al 2013;Gonzalez Montero de Espinosa et al 2013;Graff et al 2013;Mejia et al 2013;…”
Section: Behavioural Conduct/pro-social Behaviourmentioning
confidence: 99%
“…f Includes 5 case-control studies (Xi et al 2011;Zurriaga et al 2011;Yi et al 2012;Al-Ghamdi 2013;Huang et al 2013). g Includes 125 cross-sectional studies (Beets and Foley 2010;Bishwalata et al 2010;Brown et al 2010;Ferrar and Olds 2010;Hong et al 2010;Ismailov and Leatherdale 2010;Jones et al 2010;Kuhle et al 2010;Legnani et al 2010;Liou et al 2010;Melkevik et al 2010;Olds et al 2010;Pitrou et al 2010;Rivera et al 2010;Ruiz et al 2010;Shan et al 2010;Thibault et al 2010;Wilkosz et al 2010;Yen et al 2010;Zhang et al 2010;Al-Hazzaa et al 2011;Allender et al 2011;Bener et al 2011;Brown et al 2011;Carson and Janssen 2011;Chen et al 2011;Dupuy et al 2011;Fernandes et al 2011;Goyal et al 2011;Hsu and Johnson 2011;Kimbro et al 2011;Leatherdale and Papadakis 2011;Martinez-Gomez et al 2011a;McConley et al 2011;Mushtaq et al 2011;Nigg et al 2011;Peart et al 2011;…”
Section: ) Long Accelerometer-derived Sedentary Bouts (≥5 Min)mentioning
confidence: 99%